Ethical and Legal Aspect of Abortion - Olawale, Oladoye Oluwole; Landia, Natia (Caucasus Journal of Health Sciences and Public Health, 2016)
bortion is a very painful topic for women and men who find themselves facing the moral dilemma of whether or not to terminate a pregnancy. It's one of the most polarizing moral issues - most people are on one side or the other, very few are undecided. The abortion debate deals with the rights and wrongs of deliberately ending a pregnancy before normal childbirth, killing the fetus in the process. Abortion is the termination of an established pregnancy, in which the embryo is removed from the body before it becomes capable of independent life. In medicine abortion means ending a pregnancy prematurely. An abortion is when the pregnancy is ended so that it does not result in the birth of a child. Abortion is a really serious ethical issue. There are always many debates going on about abortion, from all different points of view, The main debate that is always going on is whether it is morally right to terminate a pregnancy before normal childbirth. Other debates are about the rights of the mother, the rights of the father, rights of the unborn child, and even about religious views on abortion. Background: Abortion comes from the Latin word abortion, which means to abort, miscarry, and deliver prematurely. An abortion is when the pregnancy is ended so that it does not result in the birth of a child. Abortion is the most difficult and controversial moral issues we will consider. Listen to both sides, even if that is difficult to do. Both sides have important moral insights, even if ultimately these insights are outweighed by the insights of the other side. The goal of this work is not to convince you to accept one position or the other, but to help you to understand both side. Methods: This material contains some articles from Google, and few other literatures which are well integrated and put together for better understanding and viewing of this topic. Results: There are various views on the topic of abortion which just goes beyond moral, ethical, and legal, it also encompasses religion, cultural and so on. Conclusion: In conclusion, I would say that this work or little material has helped to clarify some people’s opinion about the topic ARBORTION.